Somatic cell count, teat characteristics, milk composition and single nucleotide polymorphisms in candidate genes for mastitis in Friesian and Jersey cows - Sani, Umar Mohammed (2017)
Mastitis is a clinical condition of dairy animals characterized by inflammation of the mammary gland. It is classified as either clinical or subclinical, in which the former is associated with physical, chemical and bacteriological changes in milk as well as changes in udder morphological characteristics in dairy cows. Somatic cell count (SCC) is an important indicator of udder health and mastitis. Two types of immunity, natural or innate and acquired immunity, act together to protect the animals’ mammary gland especially at early stage of infection. The bovine toll-like receptor 4 gene (TLR4), mannose-binding lectin 1 gene (MBL1) and peptidoglycan recognition protein 2 gene (PGLYRP2) have been identified to be responsible for these immune responses. There is limited information on the single nucleotide polymorphisms (SNPs) in these genes in the Malaysian dairy cattle populations, and reports on their association with mastitis resistance or susceptibility is lacking. This study was undertaken to investigate the udder mastitis status, milk somatic cell score (SCS), teat characteristics, some milk composition traits and SNPs in three candidate genes for bovine mastitis resistance in Friesian and Jersey cows, in order to identify potential genetic markers that may be used in marker assisted selection. The Friesian and Jersey lactating cows in a commercial dairy farm were used in this research. Milk somatic cell count (SCC) was estimated using a somatic cell counter and converted to SCS, and mastitis status was established using California mastitis test (CMT). Teat lengths were measured, their functioning tested, and the orifices observed and scored. Milk composition traits were determined by infrared spectroscopy. DNA was extracted from the milk of 40 infected and 37 healthy cows, and the individual DNA samples were screened and genotyped for five SNP loci in the exons and introns of TLR4, MBL1 and PGLYRP2 using the PCR-restriction fragment polymorphism (PCR-RFLP) technique. There was no significant (P˃0.05) differences in the numbers of infected (based on California mastitis test) and functional teats between Friesian and Jersey cows reared under common management. There was also no significant differences in SCS between the breeds nor between the lactations. However, the late lactation stage milk had the highest SCS (P <0.05). Udder quarters, lactation stage and lactation number had a significant (P<0.05) effect on the teat length. The mean rear quarter teat length was significantly (P<0.05) lower than the front quarter teats. Significant relationship between teat length and quarter mastitis status was observed. The shorter the teat length, the higher was the tendency for the udder quarter to be infected. Teat-end hyperkeratosis score showed a significant differences between breeds and udder quarters. Lactation number, lactation stage, and breed had a significant (P<0.05) effects on milk lactose, but not on solid non-fat. Lactation number and lactation stage had significant (P<0.05) effects on milk fat and protein. There was no significant influence of the genotypes at the investigated loci of the TLR4, MBL 1 and PGLYRP-2 genes on SCS, milk fat, protein and lactose. There was a significant (P<0.05) association between teat condition and mastitis status. Therefore, udder morphological traits should be included in selection and breeding for mastitis resistance. A larger herd size, evaluation of more SNP loci, and analysis of data from complete lactation cycles of each animal would provide a more valid information on the effects of various influencing factors and informative markers for SCS and milk composition traits for the Friesian and Jersey dairy cattle in Malaysian.